The Utility of Online Choice Options: Do Purely Online Schools Increase the Value to Students? - William Jonathan Rauh (Arizona State University, 2011)
Online education has grown in popularity as a choice option over the past decade.  A variety of studies exist on methodologies for content delivery and on the impacts of online education for specific communities.  However, few works have considered the utility of online educational choices in comparison to physical schools.  Using an expected utility model this paper examines the value conferred to a student in an online charter school versus traditional physical schools in the same state.  Value in this case is defined as the likelihood of performing better on a standardized test.